Metal Matrix Composites - Gupta, Manoj (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Metal-based composites represent a unique way of tailoring the properties of metals, through the selection of type, size, and amount of reinforcement. In this way, the properties of metallic matrices can be adjusted depending on end applications. In view of the dynamic capabilities they can exhibit, this Special Issue will cover all aspects of metal matrix composites: synthesis (including solid, liquid, two-phase and 3D printing); secondary processing; properties (tensile, compressive, fatigue, impact, creep, tribological, etc.); corrosion behavior; and joining techniques. The main objective is to share the latest results on metal matrix composites with the research community worldwide.